2018
DOI: 10.14723/tmrsj.43.27
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of metal doped SiO<sub>2</sub> films by magnetron sputtering deposition using metal oxide mixture powder target

Abstract: Metal doped SiO2 thin films, which show strong luminescence by UV excitation, were prepared by a sputtering deposition method using metal oxide and SiO2 powder mixed targets. Electron density and temperature of the plasma using powder target was almost same independent for the mixture of powder target. However, peak intensity ratio of the plasma depends on the intensity of the powder target mixture. XPS measurements suggest that metal doped SiO2 thin films can be prepared using metal oxide and SiO2 mixture pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Figure shows the extinction coefficient and the refractive index ( n ) spectra with respect to the oxygen contents in silica films. The measured refractive index ( n ) value taken at 633 nm (deduced from ellipsometry measurements) varies between 1.4 and 1.5, which corroborates well with the data for coatings employed as AR. As expected, the extinction coefficient increases with higher energy for all oxygen contents r (O 2 ). Since the extinction coefficient is a direct function of the absorption coefficient, higher photon energy results in increasing interaction of photons and electrons to observe such a trend.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Figure shows the extinction coefficient and the refractive index ( n ) spectra with respect to the oxygen contents in silica films. The measured refractive index ( n ) value taken at 633 nm (deduced from ellipsometry measurements) varies between 1.4 and 1.5, which corroborates well with the data for coatings employed as AR. As expected, the extinction coefficient increases with higher energy for all oxygen contents r (O 2 ). Since the extinction coefficient is a direct function of the absorption coefficient, higher photon energy results in increasing interaction of photons and electrons to observe such a trend.…”
Section: Resultssupporting
confidence: 83%
“…A silica thin film has the properties to show simultaneously high optical transparency and low refractive index values, suitable to be used as optical films from the near-ultraviolet to the near-infrared spectral range. This silicon oxide layer suppresses any parasitic light absorption in the visible range due to its suitable optical band gap and transmission range. Also, low refractive index values allow these layers to be coupled with high-refractive-index materials for antireflection coating applications by minimizing the total light reflectance. In addition, due to their high optical transparency, high hydrophobicity property, and the uniformity of their surface, silica layers are extensively used in various industrial and general-purpose applications including flexible displays, optics, bioengineering, ophthalmic, and energy generation. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work, titanium oxide thin films were prepared via sputtering deposition and PLD using a powder target. [26][27][28][29][30][31] These results demonstrated that functional thin films prepared via these methods using a powder target had a quality that was almost the same as those prepared using a bulk target.…”
Section: Introductionmentioning
confidence: 71%
“…We previously reported the preparation of functional thin films under various deposition conditions, including high-quality titanium dioxide (TiO 2 ) and zinc oxide (ZnO) films via the PVD method. 15,[21][22][23][24][25][26][27][28][29][30][31][32] We also prepared A6061 thin films via magnetron sputtering 15,16) on a small JIS S25C steel (S25C) substrate. The experimental results indicated that the A6061 film can be prepared on the S25C substrate, and the ∼40 μm thick A6061 film endowed the material with high hydrogen-entry resistance in corrosive environments.…”
Section: Introductionmentioning
confidence: 99%